Healthcare providers' perspectives on the organization of health services to manage people with multiple long-term conditions in primary care settings in Kerala, India: a qualitative exploratory study - Lekha, Thoniparambil Ravindranathanpillai; Joseph, Linju; Sasidharan, Neethu Vasantha; Krishnan, Athira; Davies, Justine; Gill, Paramjit; Greenfield, Sheila; Harikrishnan, Sivadasanpillai; Thulaseedharan, Jissa Vinoda; Valamparampil, Mathew Joseph; Manaseki-Holland, Semira; Jeemon, Panniyammakal (Frontiers in Public Health, 2025)
BackgroundMultiple long-term conditions (MLTCs) are a major public health challenge globally. Complexity in managing MLTCs and their adverse consequences confronts the public healthcare systems in India. However, data from India to understand how to improve capacity to manage multiple chronic conditions are limited. We aimed to explore the challenges healthcare providers (HCPs) face in managing people with MLTCs in a south Indian primary care setting.MethodsSemi-structured interviews were conducted with HCPs in four districts of Kerala, India. Key themes and sub-themes were identified using the Framework method for thematic analysis. We categorized the systemic drivers that influenced management of patients with MLTCs in the government primary care settings as health system, organizational and individual HCPs, and patient-levels.Results33 in-depth, semi-structured interviews were conducted. Two main themes with sub-themes were found: multimorbidity preparedness (program and human resource planning; treatment guidelines and protocols; combination medicines; and handover communication between HCPs), multimorbidity care competence (awareness, implementation, and practices; attitudes of HCPs; and multimorbidity patient characteristics). Management of MLTCs at primary care was facilitated by the presence of programs for chronic respiratory conditions and depression, perceived value of electronic health records, awareness of HCPs regarding programs and patients' needs. However, several challenges at the health system level including lack of long-term planning, treatment guidelines and combination medicines, leading to fragmentation of care and poor program implementation and uptake by HCPs and patients.ConclusionOur study confirms sub-optimal health system preparedness and highlights the challenges for a transitioning primary care for managing people with MLTCs in one of India's states with a well-developed healthcare system. Our results suggest a need for improved planning and re-organization of primary health services with ongoing training support for HCPs.